Options for Tobacco Use in Afghanistan - Medici, Andre; Haven, Bernard; Rahimi, Lutfi; Ghulam, Sayed (World Bank, Washington, DC, 2019)
Many forms of tobacco are used (in varying proportions) in the different regions of Afghanistan – most commonly cigarettes, chelam and snuff. The Afghanistan Demographic and Health Survey 2015, published in 2017, provides insight into tobacco consumption across the country and allows a comprehensive analysis of some of its patterns. Generational differences in the forms of tobacco used may decrease or even disappear as younger generations grow older. As urbanization increases, cigarettes could be the main tobacco product used in the country in coming years. Almost 60 percent of male smokers consumed 10 or more cigarettes per day in 2015 (the number that indicates an addiction). Rates of tobacco use and cigarette smoking are higher in many of the provinces thatare close to Afghanistan’s borders. As the country is not a significant tobacco producer, additional research is needed to learn whether higher tobacco use in these provinces is influenced by the illicit trade with neighboring countries.